Representing the future in aging societies: Policy implications of the voting age reform in Germany - Zareh Asatryan (ZEW - Leibniz Centre for European Economic Research, 2022)
Aging societies face a fundamental challenge: How to represent future oriented policies in the politics of today? Voting age reforms and, more generally, policies that encourage the participation of the youth in politics are discussed as one solution. In this report, we study whether voting age reforms are radical enough to save us from gerontocracy. We show that there are certain policy fields that have strong age gradients. Although these are very far from being linear and often go in unexpected directions compared to a view that sees voters as simple self-interested actors.
Keywords: 330; Alternde Bevölkerung; Altersgruppe; Wahlverhalten; Politik; Präferenztheorie; Wahlrecht; Deutschland; EU-Staaten